DASAR-DASAR TEORITIS DAN FILOSOFIS SISTEM EKONOMI SYARIAH DALAM KONTEKS SISTEM EKONOMI MODERN - nurjanah, nurjanah (Insitut Pesantren Babakan cirebon, 2024)
In this paper, the author discusses the theoretical and philosophical foundations of the Islamic economic system and its integration in the context of the modern monetary system. The concept of Islamic economics is based on Islamic principles that emphasize justice, welfare, and equitable distribution of wealth. This study examines the differences between the Islamic economic system and the conventional economic system, including the existing structures, mechanisms, and instruments. The author also explains how the Islamic financial system can be an effective and efficient alternative, by reducing usury practices, maintaining the stability of the value of money, and increasing social justice. The method used is the literature method, journal articles, books, and documents, and is analyzed by identifying and comparing them with the conventional system. The purpose of this paper is to explore the principles of Islamic economics, compare economic systems, and integrate them with the modern economy. The results of this study, the Islamic economic system, like the Islamic economic philosophers associated with the modern economy, strongly considers the freedom of individual rights, and the state while still in the principles of Islam. . Keyword: sharia economic system, modern economy, Islamic principles, justice, welfare, stable value of money, social justice, inclusive